2019
DOI: 10.1175/mwr-d-18-0458.1
|View full text |Cite
|
Sign up to set email alerts
|

Where, When, and Why Did It Rain during PECAN?

Abstract: The overarching goal of the Plains Elevated Convection At Night (PECAN) field campaign was to improve understanding of the processes contributing to the nocturnal precipitation maximum in the U.S. Great Plains. This study presents the precipitation pattern surrounding PECAN and addresses the origin, timing, duration, and potential causes contributing to that pattern. It is shown that the precipitation occurs most frequently at night, as expected. The maximum in the precipitation pattern occurred in the northea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…The long lasting MCSs in our study with enhanced southerly flow associated with the trough imply that if the evolution and longevity of the MCS in the model are not well represented, errors may arise in the model treatment of Rossby wave dynamics. The importance of a linkage between MCS and upper-level Rossby wave dynamics is consistent with the recent finding of Weckwerth and Romatchke (2019) [67] that found that the top 10% of rain-producing events during the summer 2015 period that included PECAN were linked to an approaching trough. While our study suggests a coupling of the outflow and the Rossby wave, further investigations are underway to determine the nature of the error in the model (e.g., errors in the location and timing of convective initiation, gravity waves generated by MCSs, inability of the model to maintain nocturnal convection, or inaccuracies in the vertical profile of heating and divergence).…”
Section: Discussionsupporting
confidence: 89%
“…The long lasting MCSs in our study with enhanced southerly flow associated with the trough imply that if the evolution and longevity of the MCS in the model are not well represented, errors may arise in the model treatment of Rossby wave dynamics. The importance of a linkage between MCS and upper-level Rossby wave dynamics is consistent with the recent finding of Weckwerth and Romatchke (2019) [67] that found that the top 10% of rain-producing events during the summer 2015 period that included PECAN were linked to an approaching trough. While our study suggests a coupling of the outflow and the Rossby wave, further investigations are underway to determine the nature of the error in the model (e.g., errors in the location and timing of convective initiation, gravity waves generated by MCSs, inability of the model to maintain nocturnal convection, or inaccuracies in the vertical profile of heating and divergence).…”
Section: Discussionsupporting
confidence: 89%
“…b. Case selection Weckwerth et al (2019) describe the variety of physical processes associated with nocturnal CI events in the Great Plains of the United States including frontal overrunning, events forming near a parent MCS, bores or density currents, or pristine CI events. An overview of each category is described here, and example cases simulated here are shown in Fig.…”
Section: Observation Preprocessing and Sensitivity Experiments A Obse...mentioning
confidence: 99%
“…In the Great Plains, nocturnal convection initiation (CI) most commonly occurs between 0400 and 0900 UTC (Reif and Bluestein 2017), while conventional rawinsondes are typically only launched at 0000 and 1200 UTC. Moreover, most nocturnal CI events are driven by elevated ascent mechanisms such as the LLJ or undular bores (Wilson and Roberts 2006;Weckwerth et al 2019). Such features cannot be easily observed by conventional surface data, and various studies note the necessity of lowertroposphere profiling observations to improve this data gap (e.g., Wilson and Roberts 2006;Weckwerth and Parsons 2006;Keclik et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations